2016
DOI: 10.3389/fnbeh.2016.00241
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Prenatal Exposure to Undernutrition on Cannabinoid Receptor-Related Behaviors: Sex and Tissue-Specific Alterations in the mRNA Expression of Cannabinoid Receptors and Lipid Metabolic Regulators

Abstract: Maternal malnutrition causes long-lasting alterations in feeding behavior and energy homeostasis in offspring. It is still unknown whether both, the endocannabinoid (eCB) machinery and the lipid metabolism are implicated in long-term adaptive responses to fetal reprogramming caused by maternal undernutrition. We investigated the long-term effects of maternal exposure to a 20% standard diet restriction during preconceptional and gestational periods on the metabolically-relevant tissues hypothalamus, liver, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 99 publications
0
15
2
Order By: Relevance
“…In order to link these results to RP pathogenesis, the altered FASN expression induced by oxidative stress may interfere with the normal RPE morphogenesis, leading to pathological phenotype. [197][198][199][200][201][202][203] MICROVASCULAR IMPAIRMENTS The overexpression of ITGA2 could represent one of the most interesting damage caused by oxLDL, which could imply the thrombosis of retinal microcirculation, leading to cell death.…”
Section: Retinoic Acid Cycle (Rdh5 Mkv)mentioning
confidence: 99%
“…In order to link these results to RP pathogenesis, the altered FASN expression induced by oxidative stress may interfere with the normal RPE morphogenesis, leading to pathological phenotype. [197][198][199][200][201][202][203] MICROVASCULAR IMPAIRMENTS The overexpression of ITGA2 could represent one of the most interesting damage caused by oxLDL, which could imply the thrombosis of retinal microcirculation, leading to cell death.…”
Section: Retinoic Acid Cycle (Rdh5 Mkv)mentioning
confidence: 99%
“…In rodents, this type of maternal restriction has been demonstrated previously to be enough to induce long-lasting alterations in offspring [11, 14, 53, 54]. Moreover, we have recently showed that the preconceptional and gestational exposure to a moderate calorie-restricted diet increases the risk of developing features of metabolic syndrome as well as behavioral abnormalities in the offspring [47, 55]. Importantly, in the present study, we have demonstrated for the first time that a moderate maternal caloric restriction applied during the entire pregnancy alters brain endocannabinoid and/or endocannabinoid-related lipid levels at birth in male and female offspring and reduces the weight at birth.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the effects of the ECS in the adipocyte physiology and ECS deregulation in adult obesity, a few studies have been conducted to investigate the role of the ECS in the developmental origins of obesity, and they are mainly focused on the central regulation of metabolism at adulthood (19)(20)(21)(22)(23) . However, the differential effects of maternal HF diet on the ECS's components in VIS WAT, SUB WAT and BAT of the offspring during early life are unknown.…”
mentioning
confidence: 99%